Peran Komunikasi Interpersonal dalam Keluarga untuk Menanamkan Nilai Kerukunan Beragama - affandi, aguesti aulya; Davina Anabela Saswia Putri; Hanna Nazhifa Ratna Putri; Kinanti Sherin Lestari; Lathifah Nida’ Mulyasari; Renata Aulia Kamal; Sarah Nurul Fatimah; Yani Achdiani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Indonesia is a multicultural country with high religious diversity, so interfaith harmony is an important aspect in maintaining social stability. The family as the smallest social unit has a strategic role in shaping the values of tolerance and peaceful religiosity. This research aims to analyze the role of interpersonal communication in the family in instilling the value of religious harmony to family members, especially children. This research uses a literature study approach or Library research as the main method. The literature study is conducted by collecting, reviewing, and analyzing various relevant literature sources, both in the form of scientific journals, books, and other academic documents that discuss interpersonal communication in the family and the values of religious harmony. The results of the study show that interpersonal communication based on openness, empathy, and respect for differences is an effective means of transmitting religious tolerance values. This communication pattern strengthens emotional bonds in the family, so as to create a dialogical atmosphere that supports the cultivation of moderate and inclusive religious values. Thus, families through interpersonal communication contribute greatly in shaping individuals who are able to live in harmony amidst differences in beliefs, and become agents of peace in the wider community.